Phân tích đa thưc sau thành nhân tử
a] x^2-14x+24
b)36-12x+x^2
c)-18-x^2-9x
d)4-x^4
Phân tích đa thức thành nhân tử
a)x\(^2\)-2xy+x-2y
b)3x\(^3\)+6x+3-3y\(^2\)
\(x^2-2xy+x-2y=x\left(x-2y\right)+x-2y=\left(x-2y\right)\left(x+1\right)\)
\(3x^3+6x+3-3y^2=3\left[\left(x^2+2x+1\right)-y^2\right]=3\left[\left(x+1\right)^2-y^2\right]=3\left(x-y+1\right)\left(x+y+1\right)\)
Phân tích đa thức thành nhân tử
a, x\(^2\)-xy-13x-13y
b, x\(^2\)+2xy+y\(^2\)-4z\(^2\)
c, x\(^2\)-5x+6
\(a,Sửa:x^2-xy-13x+13y=x\left(x-y\right)-13\left(x-y\right)=\left(x-13\right)\left(x-y\right)\\ b,=\left(x+y\right)^2-\left(2z\right)^2=\left(x+y-2z\right)\left(x+y+2z\right)\\ c,=\left(x^2-2x\right)-\left(3x-6\right)=x\left(x-2\right)-3\left(x-2\right)=\left(x-2\right)\left(x-3\right)\)
giúp đi các bn
phân tích đa thức thành nhân tử
a, 4y^4 - 1
b, x^2 + 2xy - 9 + y^2
\(a,=\left(2y^2-1\right)\left(2y^2+1\right)\\ b,=\left(x+y\right)^2-9=\left(x+y+3\right)\left(x+y-3\right)\)
Lời giải:
a. $4y^4-1=(2y^2)^2-1^2=(2y^2-1)(2y^2+1)$
b. $x^2+2xy-9+y^2=(x^2+2xy+y^2)-9$
$=(x+y)^2-3^2=(x+y-3)(x+y+3)$
Phân tích đa thức thành nhân tử
a, 7.(3x-2)+y(3x-2)
b,x(y-x)-3(x-y)
c, x\(^2\)-6xy+9y\(^2\)
a) \(7\left(3x-2\right)+y\left(3x-2\right)=\left(3x-2\right)\left(7+y\right)\)
b) \(x\left(y-x\right)-3\left(x-y\right)=x\left(y-x\right)+3\left(y-x\right)=\left(y-x\right)\left(x+3\right)\)
c) \(x^2-6xy+9y^2=\left(x-3y\right)^2\)
a. 7(3x - 2) + y(3x - 2)
= (7 + y)(3x - 2)
b. x(y - x) - 3(x - y)
= x(y - x) + 3(y - x)
= (x + 3)(y - x)
c. x2 - 6xy + 9y2
= x2 - 3y.x.2 + (3y)2
= (x - 3y)2
Phân tích đa thức thành nhân tử
a, 3x-3+5.(x-1)
b, x\(^2\)-25+y\(^2\)-2xy
c, x\(^2\)+2xy-16a\(^2\)+y\(^2\)
a. 3x - 3 + 5(x - 1)
= 3(x - 1) + 5(x - 1)
= (3 + 5)(x - 1)
= 8(x - 1)
b. x2 - 25 + y2 - 2xy
= (x2 - 2xy + y2) - 25
= (x - y)2 - 52
= (x - y + 5)(x - y - 5)
c. x2 + 2xy - 16a2 + y2
= (x2 + 2xy + y2) - 16a2
= (x + y)2 - (4a)2
= (x + y + 4a)(x + y - 4a)
Phân tích đa thức thành nhân tử
a, 4x\(^2\)+1-y\(^2\)-4x
b, 2x\(^2\)-y\(^2\)+xy
c, x\(^2\)-3x-10
Phân tích đa thức thành nhân tử : (4x + 1)(12x – 1)(3x + 2)(x + 1) – 4
Ta có: \(\left(4x+1\right)\left(12x-1\right)\left(3x+2\right)\left(x+1\right)-4\)
\(=\left(12x^2+8x+3x+2\right)\left(12x^2+12x-x-1\right)-4\)
\(=\left(12x^2+11x+2\right)\left(12x^2+11x-1\right)-4\)
\(=\left(12x^2+11x\right)^2+\left(12x^2+11x\right)-6\)
\(=\left(12x^2+11x+3\right)\left(12x^2+11x-2\right)\)
Phân tích đa thức sau thành nhân tử : x2(x + 4)2 – (x + 4)2 – (x2 – 1)
\(x^2\left(x+4\right)^2-\left(x+4\right)^2-\left(x^2-1\right)\\ =\left(x+4\right)^2\left(x^2-1\right)-\left(x^2-1\right)\\ =\left(x^2-1\right)\left[\left(x+4\right)^2-1\right]\\ =\left(x-1\right)\left(x+1\right)\left(x+4-1\right)\left(x+4+1\right)\\ =\left(x-1\right)\left(x+1\right)\left(x+3\right)\left(x+5\right)\)
\(= (x+4)^2(x^2-1)-(x^2-1)=[(x+4)^2-1](x^2-1)\)
\(=(x+4-1)(x+4+1)(x-1)(x+1)\)
\(=(x+3)(x+5)(x-1)(x+1)\)
\(x^2\left(x+4\right)^2-\left(x+4\right)^2-\left(x^2-1\right)\)
\(=\left(x+4\right)^2\left(x^2-1\right)-\left(x^2-1\right)\)
\(=\left(x^2-1\right)\left[\left(x+4\right)^2-1\right]\)
\(=\left(x^2-1\right)\left(x+3\right)\left(x+5\right)\)
Phân tích đa thức thành nhân tử:
a, x^4+6x^3+7x^2-6x+1
b, x^4-7x^3+14x^2-7x+1
c, (x+1)^4+(x^2+x+1)^2
d, x^4+y^4+(x+y)^4
e, 12x^2-11x-36